The long-term clinical outcomes in patients after myocardial infarction in primary care - Korzh, Oleksii; Nikolenko, Yevgenii; Titkova, Anna; Pavlova, Olena; Vovk, Kira (Mangalore : Light House Polyclinic, 2021)
The aim of this study was to investigate the effect of continuous multifaceted patient-centered interventions at primary care level in patients with myocardial infarction (MI) after discharge on achieving clinical practice guideline goals and reducing the rate of hospital readmissions for cardiovascular diseases. Methods: This prospective randomized clinical study was conducted enrolled patients with MI from January 2, 2017 to December 31, 2019. Patients received medication reconciliation and education from a family physician before hospital discharge. The intervention group (IG) received continuous consultations from the family physician after discharge, whereas the control group (CG) did not. Primary outcomes included achieving blood pressure < 140/90 mmHg, low-density lipoprotein-cholesterol (LDL-C) < 70 mg/dL, and hemoglobin A1c (HbA1c) < 7% targets. The secondary outcome was major adverse cardiac events (MACEs), defined as re-hospitalization due to MI, unstable angina and stroke. Results: Two hundred and nineteen patients completed the study protocol (110 in the IG and 109 in the CG). The rate of achieving blood pressure goal was similar between the two groups. More patients in the IG achieved LDL-C and HbA1c goals than those in the CG at 1 year and 2 years post discharge. However, there was no significant difference in the cumulative incidence of MACEs between the two groups. Diabetes was the only independent predictor of rehospitalization due to a MACE. Conclusions: Family physicians interventions led to a higher rate of optimal controlled modifiable risk factors but did not significantly reduce the MACE rate in the patients with MI.
Keywords: MEDICINE; myocardial infarction; primary care; family physician; education